Pemanfaatan Tumbuhan Obat oleh Beberapa Etnis di Indonesia - Syamsul Hidayat (Journal of Tropical Ethnobiology, 2021)
Medicinal plants are one of the important commodities associated with ethnic lifestyles. This present study aimed to determine the number of medicinal plants used by ethnic groups in Indonesia and the various diseases that can be cured. Information from twenty-eight ethnic groups scattered in Indonesia were sampled in this study, consisted of 12 ethnicities from the western part of Indonesia, and 16 ethnicities from the eastern part. All medicinal plant species from 28 ethnicities were recorded, and then analyzed their similarities in both species and uses. The result showed that 608 species were documented, some of which have similar uses. Toothache, cough, and fever are the top-three most popular health problems within the society in terms of the use of medicinal plants. The most commonly used medicinal plant species were Curcuma longa, Blumea balsamifera and Alstonia scholaris.